IMPACT OF FIRM PERFORMANCE ON STOCK RETURNS: EVIDENCE FROM LARGE-CAP, MID-CAP AND SMALL-CAP STOCKS - Faniband, Muhammadriyaj; Jadhav, Pravin; Marulkar, Kedar (Indian Journal of Finance and Banking, 2023)
In this article, we analyse the impact of firm specific factors, namely, total income, net profit, and earnings per share (EPS) on stock returns of companies from the large cap, mid-cap and small- cap (LMS) categories using the panel quantile regression. We also use the ordinary least square method to compare our panel regression results. We select companies from NSE Large Cap100, NSE Mid Cap 100 and NSE Small Cap 100 Indices and each index is composed of 100 companies. These indices reflect the overall state of the Indian stock market. Our empirical analysis based on quarterly data from June 2010 to March 2022 shows some important findings. First, net sales significantly and negatively affect stock returns across the large, mid, and small cap stocks. Second, net profit and EPS have a substantial and positive impact on companies from all the categories. However, the coefficients are not significant across all quantiles. In short, the impact of firm specific factors on stock returns is not homogeneous across the LMS stocks implying that these factors do not influence stocks in a uniform way. The plausible reason may be that large, mid, and small cap companies share differences in terms of market capitalisation, growth potential and volatility. JEL Classification Codes: C31, G11, G12, G32, L25.